Conceptual exploration of the relationship between communication leadership, corporate culture and corporate reputation in the leading media government-linked companies - Md Tahir, Zainal Arifin; Abdullah, Zulhamri; Syed Alsagoff, Syed Agil; Hasan, Nurul Aien (Zes Rokman Resources, 2018)
This study will conceptually explore the role of CEOs as communication leaders among the leading media government-linked companies. The collective narratives are expected to yield ideas concerning how their respective corporate communication schemes are structured, managed and practiced. New forms of knowledge can be derived by generally address the research question: to explore the relationship between communication leadership, corporate culture and corporate reputation. The data collected should be able to address research objective: to identify and/determine the relationship between communication leadership, corporate culture and corporate reputation. The most crucial aspect is how the leading media government-linked companies are utilizing their media resources to promote corporate reputation, in view of their high vulnerability to strong institutional/political pressures. A qualitative research method is proposed because thick narrative data are needed in order to capture a robust understanding on practices of reputation management through communication. Data collection will be made through face-to-face in-depth interview. The institutional theory will be used to interpret the findings and guide the analysis is. This theory is pertinent in view of the structural preconditions that govern and give the leading media government-linked companies their legitimacy. A precedent study has used neo-institutional theories in explaining the interactions involved between the media, society and organizations in relation to CEO communication aspects. This study aspires to make a significant contribution since the amount of literature available on communication leadership, corporate culture and corporate reputation in the context of Malaysian leading media government-linked companies is relatively scant.